The Effect of Work Motivation, Education and Training on Employee Performance - Manutilaa, Korason Cici; Risambessy, Agusthina; Leuhery, Ferdy (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The importance of education and training for employees in any institution lies in the fact that an employee or staff member must contribute their best to the organization. Education and training are provided to each employee to maintain their competence. This study aims to analyze and explain the influence of education and training on employee performance, with work motivation as a mediating factor. The research was conducted at the Wokam Village Office, Kepulauan Aru District, using a saturated sampling technique, with a total sample of 30 individuals. The data analysis method used was Path Analysis. The results of the study demonstrate that education has a significant impact on employee performance. Training significantly affects employee performance. Education significantly influences work motivation. Training significantly impacts employee performance. Work motivation has a significant effect on employee performance. Education significantly affects employee performance when mediated by work motivation. Training significantly affects employee performance when mediated by work motivation.